Hybrid Semester System in MBBS Program - Ziauddin Medical College Experience - Arshia Samin Naqvi; Sadaf Fatima (ziauddin University, 2024)
Introduction With the passage of time the demands of health care delivery system are changing. The rate of scientific discovery and accumulation of knowledge is gathering speed. In order to prepare medical students as tomorrow's leaders, an effort to improve the curriculum is unavoidable.